Typification of five neotropical species of Commelina (Commelinaceae) - Hassemer, Gustavo (Phytotaxa, 2018)
Aiming at contributing to the knowledge of the neotropical Commelina, I designate here lectotypes for five species: C. bangii, C. hispida, C. leiocarpa, C. quitensis and C. reflexa. Images of the lectotypes are also provided. With the exception of C. leiocarpa, taxonomic and geographic knowledge of these species is extremely deficient.